History of the world in 1,000 objects (DK, 2020)
Offers an illustrated look at one thousand artifacts of human creation through history, from stone age tools to tablet computers, as well as an extensive timeline featuring key events in world history.
Previous edition published in 2014
At head of title: Smithsonian
Keywords: světové dějiny; hmotná kultura; prehistorická archeologie; klasická archeologie; archeologie středověku; starožitnosti; world history; material culture; prehistoric archaeology; classical antiquities; medieval archaeology; antiques; chronologické přehledy; obrazové publikace; chronological surveys; pictorial works